PROFESIONALISME AUDITOR PADA KANTOR AKUNTAN PUBLIK DILIHAT DARI PERBEDAAN GENDER, KANTOR AKUNTAN PUBLIK DAN HIRARKI JABATANNYA - ARFAN IKHSAN (Jurnal Bisnis dan Akuntansi, 2007)
The aims of the research is to obtain empirical evidence regarding there is or no difference auditor professionalism in public accountant office (KAP) if it is seen from gender, KAP and its position hierarchy. The research represent concept and modification research of Goetz et al. (1991) and replication from Darmoko’s research (2003). The sample of the research is the auditor at KAP in Medan. Intake of sampel by sampling clustered. The data was collected with method survey by using questionnaire. At least 78 respondents participated in the research, or equal to response rate 65.0 percent. The examination of hypothesis use t-test and analysis of variance. The result of the research conclude that if it is seen from gender, there is no difference professionalism. This means that between man and woman auditors have same professionalism level. Based of type KAP and position hierarchy, there is a difference of professionalism. This means among auditor in KAP which affiliate with auditor in KAP national have unequal professionalism level, and also difference of auditor position hierarchy in KAP cause difference of professionalism level.